In vivo corneal confocal microscopy as a non-invasive test to assess obesity induced small fibre nerve damage and inflammation - AYDIN, FAHRİ ONUR; TOKER, AYŞE EBRU (My University, 2022)
© 2022, The Author(s), under exclusive licence to The Royal College of Ophthalmologists.Purpose: To investigate small nerve fibre damage and inflammation at the level of the sub-basal nerve plexus (SNP) of severe obese patients and compare the results with those of healthy subjects. Methods: This cross-sectional, observational study investigated the data of 28 patients (14 out of 28 prediabetic or diabetic) with severe obesity (Body Mass Index; BMI ≥ 40) and 20 healthy subjects. Corneal nerve fibre density (CNFD), branch density (CNBD), fibre length (CNFL), nerve fibre area (CNFA), nerve fibre width (CNFW), and nerve fractal dimension (CNFrD) and dendritic cell (DC) density were evaluated using in vivo confocal microscopy (IVCM, Heidelberg Retinal Tomograph III Rostock Cornea Module). Automatic CCMetrics software (University of Manchester, UK) was used for quantitative analysis of SNP. Results: Mean age was 48.4±7.4 and 45.1 ± 5.8 in the control and obese group, respectively (p = 0.09). Mean BMI were 49.1 ± 7.8 vs. 23.3 ± 1.4 in obese vs. control group, respectively (p < 0.001). Mean CNFD, CNBD, CNFL, CNFA, CNFW were significantly reduced in obese group compared with those in the control group (always p < 0.05, respectively). There were no significant differences in any ACCMetrics parameters between prediabetic/diabetic and non-diabetic obese patients. Increased DC densities were detected in obese group compared with those in control group (p < 0.0001). There were significant correlations between BMI scores and SNP parameters. Conclusion: Imaging with IVCM is a feasible, non-invasive method to detect and quantify occult corneal nerve damage and increased inflammation in patients with obesity. This study suggests that obesity may be a separate risk factor for peripheral neuropathy regardless of DM.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Sinirbilim ve Davranış; GÖZ HASTALIKLARI; SİNİR BİLİMİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; NEUROSCIENCE & BEHAVIOR; OPHTHALMOLOGY; NEUROSCIENCES; Oftalmoloji; Duyusal Sistemler; Ophthalmology; Sensory Systems